Implementasi Pembiayaan Talangan Haji di KospinMU Surya Mentari Karanganyar Perspektif Fatwa DSN-MUI Nomor 29/DSN-MUI/VI/2002 - Lathifa, Yunia (el hisbah Journal of Islamic Economic Law, 2021)
This Study is motivated by the presence of hajj bailout products in KospinMu Surya Mentari Karanganyar. In practice, KospinMU claims that the haj bailout fund is not a qardh (loan), but the benefits obtained by cooperative members who are about to leave for Haj. This research is a type of field research. Primary data were obtained from direct interviews with KospinMU Manager Surya Mentari Karanganyar, KospinMu cooperative members, KospinMU Sharia Supervisory Board, Karanganyar Muhammadiyah Branch Leadership Advisors, as well as figures familiar with hajj bailout funding. Meanwhile, secondary data were obtained from Fatwa DSN Number 29 / DSN-MUI / VI / 2002, journals, books and scientific papers related to the concept of financing hajj management. Data analysis uses inductive methods so that researchers obtain conclusions from legal issues related to the implementation of Hajj bailout products at KospinMU. The results of this study indicate that the contract used in financing products or hajj bailout loans at KospinMU Surya Mentari Karanganyar only use ijarah contract. The amount of ujrah or fee is based on the amount of the Hajj bailout loan, not obtained from the fee for providing Hajj registration facilities.